ANALYSIS OF COGNITIVE ABILITIES OF SCHOOL-AGE CHILDREN BASED ON EATING HABITS AND NUTRITIONAL STATUS - Tri Peni; Siti Indatul Laili; Esti Dwi Jayanti; Dwi Anggita Sari (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2020)
Dietary habit is behaviors that are appropriate for the selection of the right foods so that they will provide good nutritional status. Nutrients that consist of macronutrients such as carbohydrates, proteins, fats, and micro substances such as vitamins and minerals needed by the body for the process of growth and development. The purpose of this study was to determine the relationship between eating patterns with the nutritional status and cognitive abilities of elementary school children. Cross-Sectional research design. The population in this study were all students as many as 367 students, the sampling used was a Stratified random sampling technique, a sample of 192 respondents. Data analysis uses the Spearman Rank Rho statistical test. The results of the analysis of dietary variables with nutritional status were obtained ρ (0.003) <α (0.05), so H0 was rejected, meaning that there was a relationship between eating patterns and nutritional status of school-age children, with a value of r = 0.210 which showed a high positive correlation. The results of the analysis of nutritional status variables with cognitive abilities obtained results ρ = 0.00, <α = 0.05. meaning that there is a relationship between nutritional status and cognitive learning achievement in elementary school children. Normal nutritional status can be obtained by applying a positive diet so that the intake that enters the body in accordance with the needs of the body. Children who have normal nutritional status have good cognitive abilities. Parents are the most important support in optimizing children's growth and development